Preliminary examination of reliability and validity of the Japanese Child Anxiety Impact Scale-Parent version in Japanese community sample - Okawa, S; Arai, H; Nakamura, H; Urao, Y; Reardon, T; Giles, S; Shimizu, E (Springer, 2021)
The child anxiety impact scale-parent version (CAIS-P) is a useful measure to assess the impact of anxiety on a child’s daily life; however, a Japanese version of the CAIS-P has not been developed, and whether the CAIS-P can be utilized in Eastern countries remains unascertained. The purpose of this study was to develop a Japanese version of the CAIS-P and examine its reliability and validity. Parents of 400 children (aged 7 to 15 years) from the Japanese community completed the CAIS-P. A confirmatory factor analysis indicated that the factor structure of the original CAIS-P, consisting of school activity, social activity, and home/family activity factors, provided a good fit for the Japanese version of the CAIS-P. Estimated Spearman’s correlation coefficients showed moderate correlations between the total and factor scores of the CAIS-P, anxiety symptoms (Spence Child Anxiety Scale-parent version), and depressive symptoms (Child Depression Inventory). Furthermore, the item response theory model revealed that each factor of the CAIS-P is a high information reliable measure for children with high trait anxiety. These results provide support for the Japanese version of the CAIS-P’s factorial validity, convergent validity, and reliability and its potential for application in child anxiety research in Japan.